Sociology of food - Nagla, Madhu (New Delhi Rawat publications, 2020)
The sociology of food is the study of how food relates to society, encompassing its production, distribution, and consumption, and the cultural, social, and political meanings attached to it. It examines how food practices, like diet and meal rituals, are shaped by and, in turn, shape social structures, including class, gender, and ethnic identities.